Defining authorship, debating authenticity: problems of authority from classical antiquity to the Renaissance - Berardi, Roberta; Filosa, Martina; Massimo, Davide (Beiträge zur Altertumskunde, 2020)
Frontmatter -- Acknowledgements -- Contents -- Introduction -- Semonides or Simonides? A Century–Long Controversy over the Authorship of a Greek Elegiac Fragment -- Greek Readers’ Digests (Again)? Some Lysianic ὑποθέσεις on P. Oxy. 31.2537 -- Defining a ‘Pseudo–Plato’ Epigrammatist -- Distinguishing Homonymous Writers, Detecting Spurious Works: Demetrius of Magnesia’s On Poets and Authors with the Same Name -- ‘On Sail–Flying Ships Did I Roam the Great Sea…’: The Epitaph of an Anonymous Merchant from Brundisium -- When the Author Is Not Identifiable: The Case of the Volcei Land– Register -- Theognis the Author, Traditional Wisdom, and Some Side Effects of Authority -- Beyond the Scribal Error: Clues on the History of Philodemus’ On Rhetoric, Book 1 -- The ‘Co–Authorial’ Role of Ancient Pupils, Excerptores, and Copyists in the Genuinely Menandrean Γνῶμαι μονόστιχοι -- ΛΑΒΕ ΤΗΝ ΓΡΑΦΗΝ! Book Format, Authority, and Authorship in Ancient Greek Medical Papyri -- Defensio Bessarionis: Giorgio Benigno Salviati and the Concept of Authorship in Cardinal Bessarion’s Circle -- Can Virtue Be Taught? -- Reshaping Socrates’ Authority in the Pseudoplatonica -- Letter 1 of Demosthenes and the Prayer to the Gods -- The Second Epistle of Peter: A Different Approach to Lexical Analysis -- Forged Inscriptions in Early Epigraphic Corpora -- Bibliography -- List of Contributors -- Index